Corrosion of tubes used in thermosyphon heat exchanger for waste heat recovery system: A case of internal surface - Terdtoon P. (2014)
The purpose of this article is to study the internal corrosion of tubes used in a thermosyphon heat exchanger for waste heat recovery. The thermosyphons used were made of aluminum, copper, iron, copper with internal spiral grooving, and stainless steel with internal spiral grooving. Different corrosion-protection methods were used, including tube burning and the addition of inhibitors. The thermosyphons were installed in the heat exchangers and tested over a period of 4,000 hrs at working temperatures of 150, 250, and 350°C. The Arrhenius and fouling models of Kern and Seaton were employed to analyze the data. It was found from experiments that the average corrosion rate was inversely proportional to time and depended on the temperature. The results were then compared with those taken in standard untreated tubes. Results showed that the most appropriate material for thermosyphons in waste heat recovery systems is copper tubing with a grooved internal surface. The most appropriate corrosion protection for this material is the 20-ppm inhibitor Na2HPO4 added to the working fluid of water. Fouling thermal resistance can be obtained from the correlation Zfouling = 177.78(1 - e-0.0001t), where Zfouling is the fouling thermal resistance and t is time.